Sistem Informasi Akuntansi Dan Pegendalian Internal Terhadap Kinerja Karyawan (Study Kasus Pada Pt. Bintang Kadiri) - Nurul Latifah; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2022)
This study aims to discribe whether there is a positive simultaneous influence or partially between accounting information systems, internal control and employee performance. The method used is descriptive quantitative, multiple regression analysis tools and data collection techniques in the form of questionnaires and interviews. Respondents used 58 employees with saturated samples. The results of this study are (1) Simultaneously, accounting information system and internal control affect employee performance. Partially, accounting information system affects employee performance. (3) Partially, internal control does not affect employee performance. From these results, it is recommended to the directors to improve the company's internal control system. So that employees are more orderly in carrying out the company's operational activities in accordance with the Company's Operational Standards. And it is necessary to have an internal audit to control every operational activity of the company.